Gene expression patterns and environmental enrichment-induced effects in the hippocampi of mice suggest importance of Lsamp in plasticity - Heinla, Indrek; Leidmaa, Este; Kongi, Karina; Pennert, Airi; Innos, Jürgen; Nurk, Kaarel; Tekko, Triin; Singh, Katyayani; Vanaveski, Taavi; Reimets, Riin; Mandel, Merle; Lang, Aavo; et al. (Frontiers in Neuroscience, 2015)
Limbic system associated membrane protein (Lsamp) gene is involved in behavioral adaptation in social and anxiogenic environments and has been associated with a broad spectrum of psychiatric diseases. Here we studied the activity of alternative promoters of Lsamp gene in mice in three rearing conditions (standard housing, environmental enrichment and social isolation) and in two different genetic backgrounds (129S6/SvEv and C57BL/6). Isolation had no effect on the expression levels of Lsamp. Environmental enrichment elevated the expression levels of Lsamp 1b transcript specifically in the hippocampus in B6 mice, and the same tendency existed across both mouse lines and both transcripts. Furthermore we showed that the density of cells exhibiting 1b promoter activity is remarkably higher in the subgranular zone of the dentate gyrus in the hippocampal formation which is a specific area of enrichment-induced neurogenesis in adult rodents. On the contrary to 1b, 1a promoter is selectively active in the pyramidal and granule cell layers. We provide evidence that Lsamp modulates enrichment-induced activation of Bdnf as the enrichment-induced elevation of Bdnf in the hippocampus is significantly diminished in Lsamp-deficient mice; furthermore, a significant correlation was found between the expression levels of Lsamp and Bdnf transcripts in the hippocampus and frontal cortex. Significant strain differences in Lsamp expression were detected in the hippocampus, frontal cortex and thalamus that could be related to the different behavioral phenotype of B6 and 129Sv mice. Our data provides further evidence that LSAMP is implicated in the hippocampal connectivity and plasticity thereby modulating adaptability in changing environments.